Attitudes towards the Use of Violence against Police among Occupy Wall Street Protesters. (2nd February 2018) - Maguire, Edward; Barak, Maya; Wells, William; Katz, Charles
Abstract: Although many social movement participants claim to embrace non-violent civil disobedience strategies, protesters tend to have heterogeneous views on the morality and utility of engaging in violence. In particular, protesters sometimes view violence against the police as warranted, especially if they perceive that police have treated them or their peers in a procedurally unjust or excessively forceful manner. This article examines the nature and correlates of attitudes towards the use of violence against police officers among Occupy Wall Street (OWS) protesters in New York City. Data were drawn from in-person surveys of 302 OWS participants on the 6-month anniversary of the movement in March 2012. Our findings reveal that in this context, respondents who perceive that police use unjust force against protesters are significantly more likely to endorse the use of violence against police.